Análise crítica da invocação do interesse público como fundamento para relativização de direitos e garantias fundamentais do contribuinte - Machado, Raquel Cavalcanti Ramos (2006)
This paper seeks to indicate limitations for invocation of both public interest and the supremacy of public interest over private interest in tax relations, notably when used as a foundation for rationalization of rights and fundamental guarantees of taxpaying citizens. The evolution of fundamental rights and guarantees is examined, as well as the structure of norms that support them, so as to demonstrate the existence of inherent assumptions in any limitation that is intended to be made. Considering the nature of tax relations, analysis of fundamental rights of taxpayers is emphasized from and individual and social standpoint, with brief comment upon the reality of the Social State in Brazil, a fact that may not be forgotten when one intends to impose considerable onus upon taxpaying citizens under the justification of increasing effectiveness of social rights. Considering the new constitutional hermeneutic, and in view of the reality of the Brazilian nation, it is shown that the social dimension of fundamental rights is not duly implemented, in fact, as a result of a series of factors, especially those resulting from inefficient management of funds collected, and not due to the existence of limitations to the power to tax, which, alone, may not be “rationalized” on the basis that, in this way, fundamental rights of the second and third dimension will be favored. Finally, a separate analysis is made of the term public interest and supremacy of public interest over private interest, and the role these play in the constitution, in order to demonstrate that, as they have different natures from that of rights and fundamental guarantees, they cannot be directly invoked before these, as a basis for rationalization.